Model for assessing the maturity level of digital transformation in higher education institutions: a theoretical-methodological approach - Bravo-Jaico, Jessie; Alarcón, Roger; Valdivia, Carlos; Germán, Nilton; Aquino, Janet; Serquén, Oscar; Guevara, Laurita; Moreno Heredia, Armando (Frontiers in Education, 2025)
In these times of increasing digitization and process automation, digital transformation (DT) has become a determining factor for continuous improvement and competitiveness in organizations in all areas. In the context of higher education institutions (HEIs), DT plays a fundamental role in the evolution of teaching and learning, as well as in the administrative and operational management of universities, where the use of digital tools and strategies allows greater accessibility and flexibility in education, facilitating innovation, collaboration, and knowledge generation in globalized environments. The objective of this research was to develop a theoretical-methodological framework (TMF) that allowed the creation of a model to determine the level of maturity of DT in HEIs, for which a qualitative research methodology was used, based on grounded theory, with eight phases: literature review, interviews with managers and administrators, content analysis of the interviews, definition of dimensions, definition of components, definition of actors, creation of the practical model, and determination of maturity levels. This methodology allowed the construction of a digital maturity model integrated with eight dimensions, based on the main organizational processes in higher education, with four key components of DT and four relevant actors of the university system, thus structuring a framework that allows analyzing and evaluating the state of DT in the various institutions and thus improving the quality and efficiency of their processes in the current digital era.